Rediseño de la sede administrativa del Colegio de Arquitectos del Guayas - Alvarado Cevallos, Alexis Nicole (2023)
The project consists of the redesign of an architectural school in the province of Guayas. The objective is to revitalize the existing facilities to create a modern and functional educational environment. The goal is to promote collaboration, creativity and innovation among architecture professionals and students. The project will optimize spaces, implement state-of-the-art technology, and create collaborative work areas. It will preserve the architectural identity of the building and promote excellence in the profession. The project will contribute to the development of architecture in the region and will serve as an example for other schools and training centers.